MANAJEMEN HUBUNGAN MASYARAKAT KEPOLISIAN REPUBLIK INDONESIA RESORT PONOROGO DALAM MEMBANGUN CITRA - Sinaga, Faisal Abda’u; Marantika, Nurhana; Setiawan , Veri (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
In building the image of the police, the role of Public Relations is needed that can bridge and facilitate communication between institutional interests and the needs of the community to reach an agreement to achieve these goals. This research aims to find out how the public relations management of the Indonesian National Police Resort Ponorogo in building an image. The research method used in this study is a descriptive qualitative method. The data in this study were generated through observation, documentation and interviews. The theory used in this study is the public relations strategic management model according to Grunig & Repper (2008) which consists of formulating goals, program planning, the role of communication technicians and evaluation. The results of the study show that the Public Relations of the Ponorogo Police has used Public Relations management well. In formulating the objectives, the Ponorogo Police corrected their activities, to be able to formulate better goals. In planning the program, the Ponorogo Police uses social media as a medium to inform the public about the activities that will be carried out by the Police. The role of a good technician is carried out with supervision and coordination from the leadership so that the implementation of the program can run effectively and efficiently. And ANEV which is a part that the Public Relations of the Ponorogo Police never leaves by holding ANEV once a week and also establishing good relations with community leaders to unite perceptions and avoid conflicts